Correlations between clinical features and CD4 cell count in HIV patients with tuberculosis - K., Bariha P.; C., Karua P.; M., Tudu K. (International Journal of Advances in Medicine, 2018)
Background: The correlation between tuberculosis and HIV is evident from the higher incidents of tuberculosis estimated 5-8% per year among HIV infected person with lesser CD4cell count. The high seroprevalence with tuberculosis in occurrence among AIDS patients. Methods: 100 HIV positive patients with tuberculosis who were admitted to medicine department and who visited to ARTS center were taken up for study for period of two years from December 2014 to 2016. Type of study is a observational comparative cross sectional study The investigation for HIV and TB were done as per NACO and WHO recommendation ELISA test CD4 cell counts AFB staining chest X-ray FNAC Mountoux test pleural fluid analysis Ascitic fluid analysis CSF fluid analysis USG of thorax CT scan of thorax. Results: It is seen that the maximum number of patients belong to the age group 31-40 years male 40 (40%) and female 4(4%) the common occupation in the study group was driver 36 (36%) the common constitutional symptom was weight loss physical examination reveal underweight (BMI <16-18.5) 54 (54%) among the study extra-pulmonary TB 63 (63%) X-ray chest finding pleural effusion found in 21% of patients CD4 cell counts 200-500 /µl was seen maximum number of patients. Conclusions: The CD4cell counts is important investigation in HIV and TB patients it is main investigation to know prognosis of HIV also important for initiation of ARV drugs.it is evident from this study the decrease the CD4cell counts there is increase the incidence of tuberculosis.